Three Mitochondrial Markers Reveal Genetic Diversity and Structure of Rock Carp (Procypris rabaudi) Endemic to the Upper Yangtze: Implications for Pre-release Genetic Assessment - He, Wenping; Dong, Zhiling; Ma, Tingting; Yan, Huiguo; Chen, Zhenxin; Yao, Weizhi; Cheng, Fei (Frontiers in Marine Science, 2022)
Rock carp, Procypris rabaudi, is a vulnerable carp endemic to the upper reaches of the Yangtze River and included in the National Key Protected Wildlife in 2021 as a second-class aquatic animal. Evaluating the genetic makeup of released individuals before a restocking activity is carried out is essential, and a molecular marker with simple, rapid, and universal characteristics will be helpful to the evaluation. In this study, the genetic diversity and structure of rock carp from two representative hatcheries [Yibin (YB) and Wanzhou (WZ)] and a section of the upper Yangtze [Zhuyang (ZY)] were investigated using three mtDNA markers to select one marker instead of genetic evaluation of release. The results of three mtDNA markers revealed basically the same, indicating that the level of genetic diversity in rock carp was low, and there was significant genetic differentiation between the ZY and YB. Except for Cyt b–labeled YZ (0.81) and D-loop–labeled WZ (0.59), most of the haplotypic diversity values (h) were below 0.5, the nucleotide diversity values (π) of each group were lower than 0.5 × 10-2, and the haplotype number of rock carp is 1 to 4. Among the three mtDNA markers selected, D-loop marker detected higher diversity, more haplotypes, and private haplotypes, and significant differences between the YB and WZ. The results in this study pointed out the importance of pre-release genetic evaluation and the urgency of protecting the genetic diversity of rock carp, and the D-loop marker was preferentially selected in the pre-release genetic evaluation of fish. Hatchery release is the main strategy for the recovery of rock carp populations, similar to more than 20 endemic fish species in the upper Yangtze River. This study has guiding significance for the protection and restoration of other endemic fishes in the Yangtze River by hatchery release.